Effectiveness of Anti-Retroviral Therapy in Pediatric HIV Patients; Rayong Hospital - Onprom, Narit (Journal of Health Science of Thailand, 2017)
In Thailand, there are 13,000 newborn deliveries from HIV infected mother every year. By Preventing Mother to Child Transmission (PMTCT) policy, the rate of HIV transmission from mother to child was reduced from 40 to 9 percent. However, there are many pediatric HIV infected patients who need continuum of care. The objective was to study effectiveness of Anti-Retroviral Therapy (ART) in pediatric HIV infected patients in Rayong hospital This retrospective descriptive study was designed to evaluate the ART effectiveness. Antiretroviral drug (ARV) was given to pediatric HIV patients who were enrolled in the ARV program in Rayong hospital during year 2001-2012. All of the treated partients were assessed for clinical symtomps and were clinically monitored monthly. Treatment outcome was evaluated by using clinical symptoms, Body Mass Index, percentage of CD4 and viral load. Descriptive statistics, paired t-test and One-way ANOVA test were employed in data analysis of pre-post levels of the monitored factors, and to establish correlations. There were 119 pediatric HIV patients in this program. All patients were continuously monitored of which 55.5 percent were girl, the average age was 12.1 years (1-17),S.D. at 3.22 and average age at ARV stated was 7.1(1-15),S.D. at 3.41. All were improved especially their clinical symp-toms, BMI significantly different (p<0.0001) after the ARV at 6,12,18 and 24 months. The CD4 levels were also significantly different (p<0.0001) when comparing between those before and after the ARV (at6, 12,18 and 24 months). The viral loads of pediatric HIV patients were monitored and 61.90 percent of patients were reported with<50 copied cell/ml of viral load, average hematocrit level was maintained normal and nostatistically significant at 6,12.18 and 24 months. Six patients (27.27%) develop drug resistance and two patients (9.09%) were found opportunistic infaection within 24 months. The level of CD4 may be contributed to caregiver perception in parents, as well as non-parents and Camillian Social Center. Antiretroviral therapy can improve clinical symptoms and immunological of pediatric HIV patients. Some drug resistance and a few opputunistis infection were found during the treatment. Type of caregiver was not affecting the effectiveness of caring HIV infected children including Camillian Social Center